Urodynamic and imaging findings in infants with myelomeningocele may predict need for future augmentation cystoplasty. Issue 6 (December 2019) - Corona, Lauren E.; Lee, Ted; Marchetti, Kathryn; S. Streur, Courtney; Ivancic, Vesna; Kraft, Kate H.; Bloom, David A.; Wan, Julian; Park, John M.
Summary: Introduction: Urologic issues are persistent and important causes of morbidity and mortality in patients with myelomeningocele. Classically, patients with elevated bladder pressures despite adherence to clean intermittent catheterization (CIC) and pharmacotherapy undergo augmentation cystoplasty (AC). Currently, there is little understanding of which infants are more likely to require AC later. Objective: In this context, the authors studied whether unfavorable urodynamic or imaging findings in patients with myelomeningocele during infancy could predict future AC. The authors hypothesized that infants born with elevated bladder pressures, vesicoureteral reflux (VUR), and/or hydronephrosis would be more likely to undergo AC. Study design: The authors retrospectively identified patients with myelomeningocele at their institution who were followed-up since infancy (<1 year of age), with a minimum of eight continuous years of follow-up. Standard care protocol included cystometrogram, voiding cystourethrogram (VCUG), and renal ultrasound during infancy. The primary outcome was AC for elevated bladder pressures despite attempts at more conservative management with medical therapy and CIC. Specifically, the authors evaluated for differences in augmentation rates based on gender, level of lesion, presence of detrusor leak point pressure (DLPP) or end-fill pressure (EFP) greater than 40 cm H2 O, presence of hydronephrosis, VUR, initiation of CIC, and initiation of antimuscarinics in infancy. The authors excluded patients who underwent surgical intervention for urinary incontinence. Results: A total of 97 patients met the inclusion criteria. The median follow-up time was 13.8 years. Augmentation cystoplasty was performed for 17 patients (17.5%) at a median age of 114 months (9.5 years). Detrusor leak point pressure/EFP was greater than 40 cm H2 O in 34.0% (33/97) of infant cystometrogram studies, while 30.9% (30/97) had VUR on infant VCUG and 20.6% (20/97) had hydronephrosis on infant renal ultrasound. Patients with DLPP/EFP greater than 40 cm H2 O or VUR during infancy were more likely to undergo AC ( P  = 0.02 and P  = 0.03, respectively). Binomial logistic regression revealed that DLPP/EFP greater than 40 cm H2 O (odds ratio [OR]: 4.28, 95% confidence interval [CI]: 1.34–13.62) and VUR (OR: 3.73, 95% CI: 1.18–11.77) were independent risk factors for future AC. Discussion: Infants with myelomeningocele and elevated bladder pressures and VUR should be closely monitored by urodynamic testing and imaging studies. Parents can be counseled regarding the potentially higher risk for future AC in these patients. Nonetheless, the majority of high-risk infants will safely avoid AC with conservative management.